Isolated Rearing at Lactation Increases Gut Microbial Diversity and Post-weaning Performance in Pigs - Tsai, Tsungcheng; Sales, Marites A.; Kim, Haejin; Erf, Gisela F.; Vo, Nguyen; Carbonero, Franck; van der Merwe, Marie; Kegley, Elizabeth B.; Buddington, Randy; Wang, Xiaofan; Maxwell, Charles V.; Zhao, Jiangchao (Frontiers in Microbiology, 2018)
Environment and diet are two major factors affecting the human gut microbiome. In this study, we used a pig model to determine the impact of these two factors during lactation on the gut microbiome, immune system, and growth performance. We assigned 80 4-d-old pigs from 20 sows to two rearing strategies at lactation: conventional rearing on sow’s milk (SR) or isolated rearing on milk replacer supplemented with creep feed starting on d 10 (IR). At weaning (d 21), SR and IR piglets were co-mingled (10 pens of 4 piglets/pen) and fed the same corn-soybean meal-dried distiller grain with solubles-antibiotic-free diets for eight feeding phase regimes. Fecal samples were collected on d 21, 62, and 78 for next-generation sequencing of the V4 hypervariable region of the bacterial 16S rRNA gene. Results indicate that IR significantly increased swine microbial diversity and changed the microbiome structure at d 21. Such changes diminished after the two piglet groups were co-mingled and fed the same diet. Post-weaning growth performance also improved in IR piglets. Towards the end of the nursery period (NP), IR piglets had greater average daily gain (0.49 vs. 0.41 kg/d; P < 0.01) and average daily feed intake (0.61 vs. 0.59 kg/d; P < 0.01) but lower feed efficiency (0.64 vs. 0.68; P = 0.05). Consequently, IR piglets were heavier by 2.9 kg (P < 0.01) at the end of NP, and by 4.1 kg (P = 0.08) at market age compared to SR piglets. Interestingly, pigs from the two groups had similar lean tissue percentage. Random forest analysis showed that members of Leuconostoc, and Lactococcus, at weaning best differentiated the IR and SR piglets, and were negatively correlated with d 20 Foxp3 regulatory T cell population, while positively correlated with subsequent growth performance. Our results suggest that rearing strategies may be managed so as to accelerate early-life establishment of the swine gut microbiome to enhance growth performance in piglets.